Critical Success Factors Of Implementing Industrialised Building System - Lim, Shin Sheng (2021)
Industrialised Building System (IBS) has been recognized as a promising method to enhance overall construction performance in terms of better construction quality and productivity, minimising risks related to occupational safety and health, mitigate dependency on manual foreign labour, as well as reducing construction cost effectively. Whereas the advantages seem advantageous, the idealism behind industrialised construction is far from being feasible and beneficial for the majority of contractors. The situation leaves the contractors with noticeable difficulties in implementation while trying to maintain profits and competitiveness. The latest data from Implementation Coordination Unit (ICU) dictates that 24% of public projects valued above RM 10 million manage to achieved a total IBS score of 70%. Construction Industry Development Board (CIDB) on the other hand, reports that only 14% of private projects achieved the IBS score of 50%. Therefore, the objective of this research is to identify the barriers that contractors have to cope with when implementing IBS in construction projects, and also to determine the critical success factor of implementing IBS in construction projects. Qualitative research method was selected for this research seek insight from the participant’s viewpoint; with its distinct institutional and social context intact. The target population for this study are contractors who are experienced in implementing IBS in construction projects. Semi structured interviews were carried out to collect data, and analysed using qualitative content analysis. The findings of this research show the barriers that contractors have to cope with when implementing IBS in projects are insufficient knowledge and skill, supply chain fragmentation, payment mechanism, and the lack of incentive and directives, while the critical success factors are training existing employees, establishing good working collaboration with others, powerful leadership, extensive planning and process coordination, standardisation, design and build, and utilise information technology to improve designing and communication process. The outcome of both objectives is to improve contractor’s general readiness towards the implementation of IBS in construction projects.